The Empty Box Phenomenon in the 2024 Regional Elections: Manifestation of Public Resistance to Political Oligarchy - Mustofa, Ilham; Sukmana, Oman; Soedarwo, Vina Salviana D.; Adi, Bambang Tri Sasongko (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to analyze this phenomenon through a qualitative, literature-based approach, using Jeffrey Winters' political oligarchy theory as an analytical framework. Methodology: This study uses a qualitative approach based on literature analysis. This study uses the theory of political oligarchy developed by Jeffrey Winters as the main analytical framework. The analysis process is carried out through three main stages. Main Findings: The results of the study show that the increasing number of single candidates is a manifestation of the strengthening of the power of political oligarchy, where political elites control the electoral mechanism to maintain power. However, the victory of the empty box in several regions indicates public resistance to the limitations of political choices and candidates who are considered not to meet expectations. This phenomenon has an impact on the quality of democracy and the legitimacy of local government, as well as being a warning of the need for political system reform to create a more inclusive and competitive democracy. Novelty/Originality of this study: Research on the Empty Box Phenomenon in the 2024 Election reveals manifestations of public resistance to political oligarchy, which reflects public dissatisfaction with the dominance of certain political forces and shows the potential for change in the dynamics of general elections at the regional level.